2013
DOI: 10.1186/cc13160
|View full text |Cite
|
Sign up to set email alerts
|

Persistently high venous-to-arterial carbon dioxide differences during early resuscitation are associated with poor outcomes in septic shock

Abstract: IntroductionVenous-to-arterial carbon dioxide difference (Pv-aCO2) may reflect the adequacy of blood flow during shock states. We sought to test whether the development of Pv-aCO2 during the very early phases of resuscitation is related to multi-organ dysfunction and outcomes in a population of septic shock patients resuscitated targeting the usual oxygen-derived and hemodynamic parameters.MethodsWe conducted a prospective observational study in a 60-bed mixed ICU in a University affiliated Hospital. 85 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
1
12

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(119 citation statements)
references
References 34 publications
(44 reference statements)
2
104
1
12
Order By: Relevance
“…In patients with septic shock, PvaCO2 values >6 mmHg were associated with poor outcomes in patients who had normalized their ScvO2 [46]. Changes in PvaCO2 in the first 6 hours of ICU admission may also be informative; patients with an initial PvaCO2 >6 mmHg that normalized with treatment had lower mortality [47]. These observations need confirmation in large multicenter cohorts.…”
Section: Resuscitation Triggers and Targetsmentioning
confidence: 87%
“…In patients with septic shock, PvaCO2 values >6 mmHg were associated with poor outcomes in patients who had normalized their ScvO2 [46]. Changes in PvaCO2 in the first 6 hours of ICU admission may also be informative; patients with an initial PvaCO2 >6 mmHg that normalized with treatment had lower mortality [47]. These observations need confirmation in large multicenter cohorts.…”
Section: Resuscitation Triggers and Targetsmentioning
confidence: 87%
“…37 In several studies using goal-directed therapy in sepsis, it was demonstrated that both lactate clearance and ∆Pv-aCO 2 could identify persistent tissue hypoperfusion even when the target ScvO 2 had been achieved. 34,35,38 Thus, in addition to changes in lactate, an increased PCO 2 gap could be a valuable additional parameter to predict postoperative complications in high-risk surgical patients. 39 Moreover, the PCO 2 gap as a global index of tissue perfusion could be useful to define an insufficient flow state despite normal microcirculatory parameters.…”
Section: Discussionmentioning
confidence: 97%
“…Persistence of high P (v-a) CO 2 during early resuscitation of septic shock is associated with poor outcomes [26]. …”
Section: Markers Of Global Perfusionmentioning
confidence: 99%